Associations of psychosocial stress with type 2 diabetes and glycaemic control among Ghanaians: The RODAM study. Issue 1 (20th November 2022) - Chilunga, Felix P.; Schwerzel, Pleun S.; Meeks, Karlijn A. C.; Beune, Erik; Bahendeka, Silver; Mockenhaupt, Frank; Klipstein‐Grobusch, Kerstin; Agyemang, Charles
Abstract: Background: The extent to which psychosocial stress relates to type 2 diabetes among sub‐Saharan Africans is not well understood. We assessed associations of psychosocial stresses with type 2 diabetes status and glycaemic control among Ghanaians. Methods: We used data from Research on Obesity and Diabetes among African Migrants (RODAM) study. We performed logistic and linear regression models to assess association of psychosocial stresses with type 2 diabetes and HbA1c respectively with adjustments for age, sex, education and other stresses. We also assessed moderation effects of migration status (migrant Ghanaians vs. non‐migrant Ghanaians), age, sex and education by adding interaction terms in models. Results: Four thousand eight hundred and forty one Ghanaians were included with 44% resident in Ghana, 62% women, mean age of 46 years and 10% having type 2 diabetes. Psychosocial stress at home and at work were not associated with type 2 diabetes or HbA1c levels. Negative life events in past 12 months were negatively associated with type 2 diabetes (adjusted odds ratio = 0.93, 95% CI 0.87–0.99). Perceived discrimination was positively associated with type 2 diabetes (aOR = 1.01, 95% CI 1.004–1.03). Both associations were more pronounced in men. Perceived discrimination was also positively associated with HbA1c levels, especially among those with type 2 diabetes (adjusted β = 0.01, 95% CI 0.007–0.02). Conclusions: Perceived discrimination and negative life events are associated with type 2 diabetes and glycaemic control among Ghanaians, especially in men. Further studies are needed to identify context‐specific mechanisms underlying these associations.